The rights of women in Malaysia: Special reference to article 8 of The Federal Constitution - Masum, Ahmad; Md Dahlan, Nuarrual Hilal (The Malaysian Current Law Journal Sdn Bhd, 2014)
From the very moment of her birth, the girl child confronts a world which values her existence less than that of boys.Girls face obstacles in education, nutrition, health and other areas solely because of their sex.They are viewed as having a 'transient presence' to be married young and then judged by their ability to procreate.As they mature into women, they are thrust into a cycle of dis-empowerment that is very likely to be their destiny.The issue of the rights of women remains highly divisive in most societies and regions of the world.This paper aims to examine the rights of women in Malaysia by looking at the constitutional implications of art.8 of the Federal Constitution. The methodology adopted in this paper is a,legal library based research focusing mainly on primary and secondary legal sources.The scope of this paper is limited to art.8 of the Federal Constitution dealing mainly with two issues in the context of the rights of women in Malaysia i.e the right to equal protection under the law and non-discrimination regardless of gender.The paper concludes that although the rights of women in Malaysia are accorded respect under the Federal Constitution, there is still a need for reform to stride towards the ideal of gender equality especially in the areas where laws are viewed as discriminatory and thus a hindrance to the notion of equality before the law.